Designing and Validating a Talent Management Model for Primary School Principals in Zanjan - Karimi Arghini, Hossein; Mojtabazadeh, Mohammad; Davoodi, Rasoul; Mirzaei, Noor Al-din (Iranian Journal of Educational Sociology, 2022)
Purpose: The aim of this study was to design a talent management model for primary school principals in Zanjan. Methodology: The method of the present study was a combination (qualitative and quantitative) and in terms of purpose it was an applied research. The statistical population of the qualitative section was experts who were theoretically familiar with the concept of talent management and based on purposive sampling, 17 of them were interviewed until theoretical saturation. The statistical population in the quantitative part was all primary school principals in Zanjan province (1079 people) in the academic year 2018-19 that according to Krejcie and Morgan table, 283 people were selected by stratified random sampling method. Qualitative research tools were interviews and in the quantitative part, a researcher-made questionnaire was developed based on qualitative results. The validity of qualitative results was obtained by reviewing the codings and using the agreement coefficient between the coders and for the questionnaire with face validity and reliability by Cronbach's alpha test (0.88). For the analysis of qualitative data, the method of basic theory and open, axial and selective coding were used, and for a small part of the structural equations in Amos software version 24. Findings: Qualitative data analysis identified 63 concepts and 10 central themes (environmental, cultural, motivational, educational, human resource management, personal characteristics, regulatory, communication, organizational, managerial and structural factors) that the theme Selective research also obtained effective factors on talent management. The results of structural equations also showed that organizational factors with factor load (0.85), educational (0.83) and cultural (0.80) were more important and in general, the proposed model had a good fit. Conclusion: Improving talent management requires attention to various factors that the education system by investing in organizational, educational and cultural factors can help improve the talent management of managers.